M-Pesa and mobile money in Kenya : pricing for success - Markovich, Sarit; Snyder, Charlotte ([London] : SAGE, 2016)
The Kenyan government's announcement of a new 10% tax in March 2013 threatened the future prospects of M-Pesa, Safaricom's mobile money transfer service, which had revolutionized the way money moved in Kenya. The new tax would be levied on all cash transfers but was largely targeted at M-Pesa, which controlled around 80% of the cash transfer market. In response to the new tax, Safaricom, the mobile communications market leader, announced a 10% price increase. This case presents the structure Safaricom established in order to develop a mobile money transfer service in Kenya.
Originally Published in: Markovich, S., & Snyder, C. (2013). M-Pesa and Mobile Money in Kenya: Pricing for Success. 5-213-250. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Safaricom (Firm); Pricing -- Case studies; Marketing -- Case studies; Electronic funds transfers -- Law and legislation -- Kenya -- Case studies